Apalutamide in the treatment of castrate-resistant prostate cancer: evidence from clinical trials. Issue 12 (December 2018) - Koshkin, Vadim S.; Small, Eric J.
Apalutamide (ARN-509) is a second-generation androgen receptor (AR) antagonist that was developed to inhibit AR-mediated prostate cancer cell proliferation. Following the initial promising clinical efficacy results in phase I and II clinical trials of patients with metastatic castrate-resistant prostate cancer (CRPC), apalutamide has been investigated in several phase III trials. Particular interest has focused on the development of effective therapy for the prevention of disease progression in patients with nonmetastatic (nm or M0) CRPC, especially patients who have a rapid prostate-specific antigen (PSA) doubling time that is indicative of shorter bone metastasis-free survival and associated with significant morbidity and mortality. The results from the phase III SPARTAN trial were recently published and reported a significant benefit of apalutamide relative to placebo in patients with nmCRPC and a high risk of metastatic progression. The study noted marked improvement in the primary endpoint of metastasis-free survival as well as several relevant secondary clinical endpoints, including time to symptomatic progression. These results led to the United States Food and Drug Administration (US FDA) approval of apalutamide in the nmCRPC setting in February 2018. This review summarizes the clinical development of apalutamide, culminating with the pivotal SPARTAN trial as well as other phase III trials which may further expand potential indications for this agent in the near future.